2019
DOI: 10.1126/sciadv.aav7172
|View full text |Cite
|
Sign up to set email alerts
|

The role of aseismic slip in hydraulic fracturing–induced seismicity

Abstract: Models for hydraulic fracturing–induced earthquakes in shales typically ascribe fault activation to elevated pore pressure or increased shear stress; however, these mechanisms are incompatible with experiments and rate-state frictional models, which predict stable sliding (aseismic slip) on faults that penetrate rocks with high clay or total organic carbon. Recent studies further indicate that the earthquakes tend to nucleate over relatively short injection time scales and sufficiently far from the injection z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
246
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(265 citation statements)
references
References 63 publications
19
246
0
Order By: Relevance
“…Such stress drop/rupture velocity variation is consistent with the results of both laboratory and meso-scale experiments that aseismic slip near the injection point gradually transitions to seismic slip at further distances with a continuum of slip speeds (15,18). Recent modeling efforts have also demonstrated the scenario as numerically plausible (14,16). Thus, we interpret EHWs as events that nucleate through loading of adjacent aseismic slip, rupture at slower slip speeds and/or lower stress drops, and bridge (induced) aseismic slip at the wellbore to typical seismic rupture on more distal faults.…”
Section: The Above Reasoning Begs the Question Of What Is The Most VIsupporting
confidence: 85%
See 2 more Smart Citations
“…Such stress drop/rupture velocity variation is consistent with the results of both laboratory and meso-scale experiments that aseismic slip near the injection point gradually transitions to seismic slip at further distances with a continuum of slip speeds (15,18). Recent modeling efforts have also demonstrated the scenario as numerically plausible (14,16). Thus, we interpret EHWs as events that nucleate through loading of adjacent aseismic slip, rupture at slower slip speeds and/or lower stress drops, and bridge (induced) aseismic slip at the wellbore to typical seismic rupture on more distal faults.…”
Section: The Above Reasoning Begs the Question Of What Is The Most VIsupporting
confidence: 85%
“…Laboratory and experimental work, including larger meso-scale experiments, have shown that loading can generate a continuum of slip behavior ranging from aseismic to seismic, and in some cases aseismic slip can transition to seismic slip within a single slip episode (15,18). In addition, modeling studies of aseismic slip in fluid injection environments have quantitatively validated laboratory aseismic slip observations, proving that (1) the aseismic slip front could outpace the diffusion front, and (2) a limited amount of aseismic slip is sufficient to trigger larger magnitude events in cases where it interacts with nearby, larger faults (14,(16)(17). However, to the best of our knowledge, direct field observations of aseismic or slow slip signals prior to the onset of seismic slip have not been clearly documented outside of experimental injection environments.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…While previous studies have provided overall knowledge of the ambient stress field in Oklahoma and southern Kansas, a high‐resolution stress map is needed to systematically assess fault criticality under the local stress field. This is especially important with the growing evidence that poroelastic stress (e.g., Barbour et al, ; Deng et al, ; Goebel et al, ; Segall & Lu, ) and aseismic creep propagation (e.g., Cappa et al, ; Eyre et al, ) could, in part, drive some of the induced seismicity. In this study, we develop a stress map with relatively high spatial resolution using a suite of 2,047 focal mechanism solutions obtained from Oklahoma and southern Kansas, allowing for more precise quantitative analysis of the fault stress state.…”
Section: Introductionmentioning
confidence: 99%
“…• For microseimic monitoring (Eyre et al, 2019;White and Foxall, 2016), earthquakes with different signatures but with roughly the same hypocenter x 0 , i.e., repeating earthquakes that rupture the same fault zone, generate required instances w(t; τ ) (see Fig. 1a).…”
Section: Time Lapse Monitoringmentioning
confidence: 99%